1996
DOI: 10.2307/3870211
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Susceptibility to Viral Disease of b-1,3-Glucanase-Deficient Plants Generated by Antisense Transformation

Abstract: Antifungal class I [beta]-1,3-glucanases are believed to be part of the constitutive and induced defenses of plants against fungal infection. Unexpectedly, mutants deficient in these enzymes generated by antisense transformation showed markedly reduced lesion size, lesion number, and virus yield in the local-lesion response of Havana 425 tobacco to tobacco mosaic virus (TMV) and of Nicotiana sylvestris to tobacco necrosis virus. These mutants also showed decreased severity of mosaic disease symptoms, delayed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(35 citation statements)
references
References 44 publications
2
31
0
2
Order By: Relevance
“…Many studies have confirmed that the b-1,3-glucanases play a role in mechanism involved in resistance to pathogenic infection, which are coordinately induced in response to pathogenic infection and it can be considered as pathogenesis-related protein of tobacco [28][29][30][31][32]. Our results demonstrated that that the activity of b-1,3-glucanases obviously increased in the presence of NNM (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Many studies have confirmed that the b-1,3-glucanases play a role in mechanism involved in resistance to pathogenic infection, which are coordinately induced in response to pathogenic infection and it can be considered as pathogenesis-related protein of tobacco [28][29][30][31][32]. Our results demonstrated that that the activity of b-1,3-glucanases obviously increased in the presence of NNM (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…The constitutive plasma membrane-localized callose synthase enzyme catalyses the formation of this, P-1,3-glucan polymer and requires both increased levels of the primer P-furfuryl-P-glucoside and Ca2+ for activity (Kauss, 1990;Ohana et al, 1993). Blockage of plasmodesmata with callose is an essential component of the defense response required to impede cell-to-cell movement of viruses (Beffa et al, 1996).…”
Section: Cell Wall Fortificationmentioning
confidence: 99%
“…Some components of this response, such as the antifungal class I b-1, 3-glucanases (GLU I) and chitinases (CHN I), which are vacuolar PR-related proteins, act in concert to defend against a specific class of pathogens, fungi. Studies of deficient mutants suggest that GLU I may have dual defense-and counter defense-functions (Beffa et al, 1996;Iglesias and Meins, 2000a, b). Local induction of GLU I in response to virus infection actually increases the susceptibility of the plant to virus and appears to act, at least in part, by degrading callose at the cell surface important for reducing plasmodesmatal transport and virus spread (Bucher et al, 2001).…”
Section: Introductionmentioning
confidence: 99%